The Middle east respiratory syndrome (MERS)- Threat to Asian countries - Pandurangan, Hariprasath (Indian Journal of Nursing Sciences, 2024)
The Middle East respiratory syndrome (MERS) is a viral respiratory disease caused by a novel coronavirus (MERS‐CoV) a single-stranded RNA virus of the genus Betacoronavirus that was first identified in Saudi Arabia in 2012. Coronaviruses are a large family of viruses that can cause diseases ranging from the common cold to Severe Acute Respiratory Syndrome (SARS). Typical MERS symptoms include fever, cough, and shortness of breath. Gastrointestinal symptoms, including diarrhea, have also been reported. Some laboratory-confirmed cases of MERS-CoV infection are reported as asymptomatic, meaning that they do not have any clinical symptoms, yet they are positive for MERS following a laboratory test. Approximately 35 % of reported patients with MERS have died. Although the majority of human cases of MERS have been attributed to human-to-human infections in health care settings, current scientific evidence suggests that dromedary camels are a major reservoir host for MERS-CoV and an animal source of MERS infection in humans. However, the exact role of dromedaries in the transmission of the virus and the exact route(s) of transmission is unknown. The virus does not seem to pass easily from person to person unless there is close contact, such as occurs when providing unprotected care to a patient. Health care-associated outbreaks have occurred in several countries, with the largest outbreaks seen in Saudi Arabia, United Arab Emirates, and the Republic of Korea. No specific treatment for MERS-CoV infection is currently available. Clinical management includes supportive management of complications and implementation of recommended infection prevention and control measures.